A meta-analysis of the incidence of venous thromboembolic events and impact of anticoagulation on mortality in patients with COVID-19 (2020)
Background: The incidence of venous thromboembolic events (VTE) in patients with COVID-19 is generally high but varies markedly. However, the relationship between anticoagulation and mortality in patients with COVID-19 is still unclear. Methods: We performed a systematic review and meta-analysis to determine the incidence of VTE and evaluate the role of anticoagulation in patients with COVID-19. Random effects models were used to determine overall pooled estimates and 95% confidence intervals (CIs). Results: After a database search, 25 observational studies (20 on VTE incidence and 5 on the relationship between anticoagulation and mortality) were included. The pooled incidence rates of VTE, pulmonary embolism (PE), and deep vein thrombosis (DVT) in hospitalised COVID-19 patients were 21% (95% CI 15–27%), 15% (95% CI 10–20%), and 27% (95% CI 19–36%), respectively. A meta-analysis of five studies found that anticoagulation was not associated with an increased risk of mortality in hospitalised COVID-19 patients (RR = 0.86, 95% CI, 0.69–1.09, P = 0.218; I2 = 47.4%). Conclusions: In conclusion, the incidence of VTE among hospitalised COVID-19 patients was high. Clinical trials are urgently needed to evaluate the roles of prophylactic and therapeutic anticoagulation in COVID-19.